Cognitive and pragmatic characteristic of S. King's work "Pet Cematary": experience in comparative analysis of original and translated texts - Sofiia N. Semenova; Anna V. Zhandarova; Denis N. Sekunov (Publishing house "Sreda", 2023)
The work is devoted to the analysis of the novel by S. King "Pet Cematary" in the original English and Russian versions in a comparative aspect. The purpose of the article is a cognitive-pragmatic characterization of texts based on lexical units. The authors of the study solve the following tasks: a comparative analysis of the linguistic features of the texts of the work, the presentation of the most striking examples from a linguocultural point of view, the semantic interpretation of lexical units. The novelty of the study lies in the attempt to analyze the text of the novel in two languages in a comparative way (the authors of the article chose two versions of the translation into Russian, made by I. A. Bagrov and T. Yu. Pokidaeva). The data obtained during the study of texts reflect the culture and lexicon of the contemporaries of the authors of the translation, which is important for modern scientific research in the field of studying vocabulary, both from the structural and content sides. In the process of reviewing the material, the methods of continuous sampling, classification and interpretation were used. The analysis carried out helped to reveal the specifics of the perception of information in different periods of time. The lack of accuracy in the transfer of lexical units in translated works determines the need for further research in this direction.